Get to Know the Marine Tourism Village of Miang Island, Your Charm is Really Charming - Jamaluddin; Siska Melynda; Wulandari; Yurika Wahyuni; Deny Christian Ingan (Prospect Publishing, 2023)
Miang Island is a Marine Tourism Village located in Sangkulirang District, East Kutai Regency, East Kalimantan Province. The purpose of this article is to introduce the Miang Island Marine Tourism Village both locally and abroad. To be able to get to know the Miang Island Marine Tourism Village, various qualitative and quantitative data were collected. Data collection is carried out by surveying, observation, and document study methods. The survey was conducted with interviews and questionnaires. Observation is carried out by visiting directly the object of devotion. Meanwhile, document studies are carried out to obtain more accurate data support. Miang Island Marine Tourism Village with a very beautiful natural panorama and has not been touched by many tourists. Therefore, it is necessary to introduce it to become a leading tourist attraction in East Kalimantan Province. Miang Island Marine Tourism Village is domiciled on the sea, a unique village. On Miang Island, you can enjoy sunrise and sunset. In addition, there are also snorkeling areas, gusung, tellibo, and lighthouse towers.